2001
DOI: 10.1136/bmj.322.7298.1327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long term consumption of probiotic milk on infections in children attending day care centres: double blind, randomised

Abstract: Objective To examine whether long term consumption of a probiotic milk could reduce gastrointestinal and respiratory infections in children in day care centres. Design Randomised, double blind, placebo controlled study over seven months. Setting 18 day care centres in Helsinki, Finland. Participants 571 healthy children aged 1-6 years: 282 (mean (SD) age 4.6 (1.5) years) in the intervention group and 289 (mean (SD) age 4.4 (1.5) years) in the control group. Intervention Milk with or without Lactobacillus GG. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
481
1
31

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(524 citation statements)
references
References 21 publications
11
481
1
31
Order By: Relevance
“…Indicating a stimulation of the immune system, these outcomes can be important for several population groups, for example elderly, stressed workers and children that are susceptible for infections. An enhancement of the immune system induced by probiotic bacteria can reduce duration and severity of infectious diseases (Schiffrin et al, 1997;Hatakka et al, 2001;Turchet et al, 2003). The expression of the specific cellular surface markers (CDs) remained unaffected through this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indicating a stimulation of the immune system, these outcomes can be important for several population groups, for example elderly, stressed workers and children that are susceptible for infections. An enhancement of the immune system induced by probiotic bacteria can reduce duration and severity of infectious diseases (Schiffrin et al, 1997;Hatakka et al, 2001;Turchet et al, 2003). The expression of the specific cellular surface markers (CDs) remained unaffected through this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a mean (s.d.) of 5.8 (4.5) days of illnesses among Finnish children aged 1 to 6 years, during a 7-month follow-up (Hatakka et al, 2001). Using this latter estimate of the mean and the estimate of 4.5 for the s.d.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their popularity, there is a need for controlled studies on specific probiotic strains, in settings and modalities that are similar to how probiotics are actually consumed in the United States (Pedone et al, 1999;Hatakka et al, 2001;Weizman et al, 2005;Lin et al, 2009). We have previously found that providing an intervention in the form of a yogurt drink greatly increases compliance, and presents parents with a simple alternative to traditional probiotic supplemental pills or capsules (Merenstein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Children also represent a main target of studies that investigate the effects of probiotics on human health, because of the importance of limiting the spread of diseases especially during wintertime, reducing missed days at school, and decreasing the need of antibiotics [43][44][45].…”
Section: Probiotics and The Immune Responsementioning
confidence: 99%